Localization of folds and cracks in thin metal films coated on flexible elastomer foams - Vandeparre, Hugues (Advanced materials (Deerfield Beach, Fla.), 2013)
Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.